Abnormal Fibrinogen Level as a Prognostic Indicator in Coronavirus Disease Patients: A Retrospective Cohort Study - Long, Wei; Yang, Jie; Li, Zhengwei; Li, Jinpeng; Chen, Sichao; Chen, Danyang; Wang, Shipei; Li, Qianqian; Hu, Di; Huang, Jianglong; Zeng, Wen; Guo, Liang; et al. (Frontiers in Medicine, 2021)
Purpose: The coronavirus disease (COVID-19) pandemic poses a global threat, and identification of its prognostic biomarkers could prove invaluable. Fibrinogen (FIB) could be one such indicator as coagulation and fibrinolysis abnormalities are common among COVID-19 patients. We examined the role of FIB levels in the prognosis of COVID-19. Methods: This retrospective cohort study enrolled 1643 COVID-19 patients from the Leishenshan Hospital in Wuhan, China. The follow-up was conducted from February 8, 2020 to April 15, 2020. The cohort was divided into three groups according to the FIB level on admission, and associations with mortality and disease severity were determined using Cox and logistic regression analyses, respectively. Further, Kaplan–Meier (K–M) analyses by log-rank tests were used to assess the survival of patients with varying FIB levels. Results: Patients with FIB < 2.2 g/L (hazard ratio [HR]: 9.02, 95% confidence interval [CI]: 1.91–42.59, P = 0.006) and > 4.2 g/L (HR: 4.79, 95% CI: 1.14–20.20, P = 0.033) showed higher mortality risks compared to those with FIB between 2.2–4.2 g/L. The survival curves showed similar results in K–M analyses (P < 0.001). Additionally, an elevated FIB level was associated with a greater risk of developing critical disease (odds ratio: 2.16, 95% CI: 1.04–4.46, P = 0.038) than a FIB level within the normal range. Conclusion: Abnormal FIB levels may be associated with mortality risk among COVID-19 patients and could predict critical disease development. Thus, assessment of FIB levels may assist in determining the prognosis of COVID-19 patients.